Novel targeted therapeutics for mantle cell lymphoma – What's on the horizon?. Issue 3 (3rd March 2016) - El Halabi, Layal; Ghez, David; Ribrag, Vincent
ABSTRACT: Major advances have significantly improved the outcome of mantle cell lymphoma (MCL). Incorporation of rituximab to CHOP regimen, the adoption of high dose cytarabine with frontline autologous stem cell transplantation in young patients, maintenance rituximab or bortezomib based chemotherapy in elderly patients, improved the disease outcome. Bortezomib, lenalidomide, temsirolimus and ibrutinib have proven their efficacy and are approved for the use in refractory or relapsed MCL patients. Several other molecules are currently being evaluated such as cyclin dependent kinase 4/6 (CDK4/6), phosphoinositide 3-kinase (PI3K), B cell lymphoma-2 (BCL2) and Poly ADP-ribose polymerase (PARP) inhibitors. Unfortunately, we don't have specific biomarkers that could reveal which of the underlying pathways or genetic alterations are mostly involved in each individual case of MCL. Efforts should be done in this field aiming to an optimal personalized therapy.